Dynamizing Contemporary Ijtihad: Inclusivity and the Positivization of Islamic Law in Indonesia’s National Legal System - Caniago, Sulastri; Yaswirman, Yaswirman; Efrinaldi, Efrinaldi; Warman, Arifki Budia; Efendi, Roni (As-Siyasi: Journal of Constitutional Law, 2025)
The Indonesian legal system comprises three main components: customary law, Islamic law, and European law. These three systems serve as foundational elements in the construction of a holistic and comprehensive national legal framework through national legal politics. This study aims to examine the position and role of Islamic law in Indonesia, focusing on Ijtihad in the context of social change and the positivization of Islamic law. Employing a normative juridical method, this research relies on secondary data sources, including primary and secondary legal materials. The findings reveal that the adaptive and dynamic character of Islamic law allows it to grow and develop in the Indonesian legal system, which is transforming codification and official and binding legal enforcement. This development cannot be separated from the direction and policy of legal politics that influence the process of Islamic legal legislation. Although its application is not yet comprehensive and is still limited to certain fields, Islamic law has gained recognition in the form of independence, legitimacy, and authority as part of national law